Alcohol consumption and risk of psoriasis: Results from observational and genetic analyses in more than 100,000 individuals from the Danish general populationCapsule Summary - Alexander Jordan, BSc; Charlotte Näslund-Koch, MD; Signe Vedel-Krogh, PhD; Stig Egil Bojesen, DMSc; Lone Skov, DMSc (Elsevier, 2024)
Background: Psoriasis is associated with high alcohol consumption, but the causality of this relationship is unclear. Objective: We aimed to use a Mendelian randomization approach to investigate the causal effects of alcohol on incident psoriasis. Methods: We included 102,655 adults from the prospective Copenhagen studies. All participants filled out a questionnaire on alcohol consumption, were physically examined, and had blood drawn for biochemical and genetic analyses. We created a genetic instrument based on the number of fast-metabolizing alleles in alcohol dehydrogenase 1B and alcohol dehydrogenase 1C, known to be associated with alcohol consumption, to test whether alcohol consumption was causally associated with psoriasis. Results: Observationally, we found an increased risk of incident psoriasis among individuals with high alcohol consumption compared to those with low alcohol consumption with a hazard ratio of 1.30 (95% confidence interval 1.05-1.60) in the fully adjusted model. Using genetic data to predict alcohol consumption to avoid confounding and reverse causation, we found no association between number of fast-metabolizing alleles and risk of psoriasis. Limitations: Alcohol consumption was self-reported and psoriasis was defined using the International Classification of Diseases 10th revision and 8th revision codes. Conclusion: Alcohol consumption is observationally but not causally associated with incident psoriasis.